Poetry Wars - Sylvia R. Sherno (Studies in 20th & 21st Century Literature, 2012)
The status of poetry in Spain over the last several decades has provided fodder for a surprisingly contentious dispute, perhaps particularly remarkable for devotees and critics on these shores, where poetry has a limited readership…
Keywords: poetry in Spain; poetry; modern poetry; contemporary poetry; 21st century Spanish poetry; twentyfirst century Spanish poetry; poetry from Spain; dispute; criticism